ADAM8 expression in breast cancer derived brain metastases: Functional implications on MMP‐9 expression and transendothelial migration in breast cancer cells. Issue 4 (31st October 2017) - Conrad, Catharina; Götte, Malena; Schlomann, Uwe; Roessler, Marion; Pagenstecher, Axel; Anderson, Peter; Preston, Jane; Pruessmeyer, Jessica; Ludwig, Andreas; Li, Ran; Kamm, Roger D.; Ritz, Rainer; et al.
Abstract : Metastatic breast cancer affects long‐term survival and is a major cause of cancer death for women worldwide. The Metalloprotease‐Disintegrin ADAM8 promotes breast cancer development and brain metastasis in a mouse breast cancer model. Here, abundant ADAM8 expression was detected in primary human breast tumors and associated brain metastases. To investigate the function of ADAM8 in metastasis, MB‐231 breast cancer cells with ADAM8 knockdown (MB‐231_shA8) and scramble control cells (MB‐231_shCtrl) were analyzed for their capability to develop metastases. In vitro, formation of metastatic complexes in hanging drops is dependent on ADAM8 and blocked by ADAM8 inhibition. MB‐231_shA8 in contrast to MB‐231_shCtrl cells were impaired in transmigration through an endothelial and a reconstituted blood‐brain barrier. Out of 23 MMP and 22 ADAM genes, only the MMP‐9 gene was affected by ADAM8 knockdown in MB‐231_shA8 cells. Following re‐expression of wild‐type ADAM8 in contrast to ADAM8 lacking the cytoplasmic domain in MB‐231_shA8 cells caused increased levels of activated pERK1/2 and pCREB (S133) that were associated with elevated MMP‐9 transcription. Application of ADAM8 and MMP‐9 antibodies reduced transmigration of MB‐231 cells suggesting that ADAM8 affects transmigration of breast cancer cells by MMP‐9 regulation. ADAM8‐dependent transmigration was confirmed in Hs578t cells overexpressing ADAM8. Moreover, transmigration of MB‐231 and Hs578t cells was significantly reduced for cells treated with an antibody directed against P‐selectin glycoprotein ligand (PSGL‐1), a substrate of ADAM8. From these data we conclude that ADAM8 promotes early metastatic processes such as transendothelial migration by upregulation of MMP‐9 and shedding of PSGL‐1 from breast cancer cells. Abstract : What's new? Brain metastasis remains a major complication following primary malignancies, with unfavorable impacts on patient survival. Better understanding of factors involved in the spread of malignant disease is needed, however, before new prognostic and therapeutic opportunities can be identified. Here, the metalloprotease‐disintegrin ADAM8 was found to be highly expressed in brain metastases from different primary origins in human tumors. In breast cancer cells, ADAM8 promoted metastatic processes, regulating endothelial adhesion of breast cancer cells via shedding of the P‐selectin ligand PSGL‐1 and increased MMP‐9 activity. ADAM8 may be a suitable prognostic marker and therapeutic target in brain metastasis prevention.